Hydrogen storage mechanism and lithium dynamics in Li12C60 investigated by μSR. (August 2015) - Gaboardi, Mattia; Cavallari, Chiara; Magnani, Giacomo; Pontiroli, Daniele; Rols, Stephane; Riccò, Mauro
Abstract: The lithium cluster intercalated fulleride Li12 C60 was investigated by means of Muon Spin Relaxation (μSR) spectroscopy with the intent of unveil its hydrogen storage mechanism. Thanks to the well-known propensity of positive muons to form Muonium, a light isotope of the hydrogen atom, the final stages of the absorption process can be probed. The appearance of a slow oscillating signal in the time evolution of the muon polarization indicates the presence of Li–Mu covalent pair, never observed before in lower doped Li fullerides, which mimics the formation of LiH at the first stage of hydrogen chemisorption in the material. In addition, the μSR signal shows a clear transition above 150 K, compatible with a thermally activated Li cluster rearrangement. The combined Inelastic Neutron Scattering analysis suggests that tetrahedral Li clusters may undergo a progressive melting upon heating, which could favour room temperature ionic diffusion.